Предмет:
МатематикаАвтор:
аноним(b / (a^2 - ab) - 2 / (a - b) - a / (b^2 - ab) : (a^2 - b^2) / 4ab = 4 / (a + b).
(b / (a^2 - ab) - 2 / (a - b) - a / (b^2 - ab) : (a^2 - b^2) / 4ab = b / a * (a - b) - 2 / (a - b) - a / b * (b - a) : (a - b) * (a + b) / 4ab = b / a * (a - b) - 2 / (a - b) + a / b * (a - b) : (a - b) * (a + b) / 4ab = (b^2 - 2ab + a^2) / ab * (a - b) : (a - b) * (a + b) / 4ab = (a - b)^2 * 4ab / ab * (a - b) * (a - b) * (a + b) = 4 / (a + b).
4 / (a + b) = 4 / (a + b) - тождество доказано.
Автор:
jacobsmithДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть